Phenolic acids accumulation and their antioxidant potential in wheat cultivars under the reduced and optimal nitrogen levels - Marija Kovačević Babić; Daniela Horvat; Dario Novoselović; Filip Horvat; Krešimir Dvojković (Croatian Journal of Food Science and Technology)
Three common wheat cultivars (Triticum aestivum L.) were grown under the reduced and optimal nitrogen (N) levels during 2018/2019 vegetation season. In this study, phenolic compounds were analysed as soluble-free and insoluble-bound fractions, because the majority of them are found in cereals in these forms. Total phenolic content in both extracts (TPC) was determined using the Folin-Ciocalteu reagent, while the antioxidant activity (AOA) of phenolics was evaluated using the 2,2–diphenyl–1–picrylhydrazyl radical scavenging test. The composition and content of phenolic acids (PAs) was analysed by HPLC. On average, TPC and AOA values were several times higher in the insoluble–bound extract compared to the soluble–free one (163.2 mg GAE/100 g DM vs. 60.7 mg GAE/100 g DM, and 48.5% vs. 17.6%, respectively). Soluble–free PAs ranged from 4.0 mg/100 g DM (p–coumaric acid) to 4.6 mg/100 g DM (p–hydroxybenzoic acid), while insoluble–bound PAs content was much higher, ranging from 2.2 mg/100 g DM (caffeic acid) to 56.5 mg/100 g DM (ferulic acid). For phenolic extracts, TPC, AOA and almost all PAs content was higher under the reduced nitrogen levels. In general, insoluble–bound PAs were more susceptible to higher nitrogen supply than soluble-free ones. Although cultivars showed a similar response to increased nitrogen rate, considerable variability in their phenolic properties was observed.